Managing Research and Development for Core Competence Building in an Organization - Ahuja,I.P.S (Universidad Alberto Hurtado. Facultad de Economía y Negocios, 2011)
The uncertainties due to globalization of Indian market after economic reforms have led to drastic changes in the approach of manufacturing organizations for developing various competencies to get competitive advantage. These formidable changes have left the organizations with no choice but to upgrade the existing systems, products and technologies for their survival. The external acquisition of technology in the initial stages may be desirable or even necessary in the high technology areas, but no industry can prosper in the long run unless it builds up a self reliant base for carrying out indigenization of process and product technologies. Technology upgradation has become mandatory for economic development, industrial growth, enhanced corporate image, more flexible responses, strategic self-reliance and sustained competitiveness of an enterprise. The present study is aimed at highlighting the need of R&D initiatives in Indian enterprises for harnessing competencies through indigenized R&D.